2014
DOI: 10.4238/2014.september.29.8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic variation of the C677T and A1298C polymorphisms in the methylenetetrahydrofolate-reductase (MTHFR) gene in southwestern Mexico

Abstract: ABSTRACT. In this study, we examined the distribution of genotype and allele frequencies of the C677T and A1298C polymorphisms in the methylenetetrahydrofolate-reductase gene (MTHFR) in two ethnic groups in the State of Guerrero, Mexico, which were compared with those of the Mestizo population of the region. A comparative study was conducted on 455 women from two ethnic groups and a group of Mestizo women of the State of Guerrero, Mexico: 135 Nahuas, 124 Mixtecas, and 196 Mestizas. Genotyping of both polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
1
7
0
1
Order By: Relevance
“…[18]. Например, минорная Т-аллель локуса 677С>T наиболее распространена среди жителей Италии и Мексики, в культуре питания которых значимый удельный вес занимает растительная пища [15]. Вместе с тем данные популяции характеризуются сбалансированным питанием, включающим растительные, мясные и морепродукты.…”
Section: генетика и протеомикаunclassified
“…[18]. Например, минорная Т-аллель локуса 677С>T наиболее распространена среди жителей Италии и Мексики, в культуре питания которых значимый удельный вес занимает растительная пища [15]. Вместе с тем данные популяции характеризуются сбалансированным питанием, включающим растительные, мясные и морепродукты.…”
Section: генетика и протеомикаunclassified
“…Both polymorphisms have been associated with reduced enzyme activity, particularly the C677T polymorphism, which imparts thermolability to the enzyme [ 2 , 3 ]. Worldwide studies of these variants have shown that the Mexican Mestizo population has the highest frequency of the 677T allele (44–61%), and the lowest frequency of the 1298C allele (7–11.7%) [ 4 8 ]. In particular, the C677T polymorphism has been implicated in several diseases, including neural tube defects (NTDs), cardiovascular diseases, hypertension and various types of cancer, among others [ 4 , 9 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the Amerindian genome has largely contributed to the presence of the 677T allele in the Mexican-Mestizo population [ 7 , 8 , 13 , 16 ]. Most of Mexicans are a mixed population derived mainly from Amerindian, European, and African ancestries, whose proportion vary largely across the country, with a clear increasing Amerindian ancestry gradient from North to South [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit frequent in different populations, these polymorphisms have shown great ethnic and geographical variability (Sebastio et al, 1995;Franco et al, 1998;Franco et al, 1999;Dilley et al, 2001;Franco and Reitsma, 2001;Miranda-Vilela, 2012;Antonio-Véjar et al, 2014). As the Brazilian population is very mixed, primarily from five centuries of interethnic crosses among Europeans, Africans and Amerindians, and this miscegenation can influence the distribution of certain polymorphisms (Lordelo et al, 2012;Barbosa et al, 2014), the objective of this study was to investigate the role of MTHFR (C677T, A1298C) and CBS (T833C/844ins68, CBS G919A) polymorphisms in serum levels of folic acid, vitamin B12 and Hcy in Brazilian patients with a diagnosis of thrombosis, and to verify a possible association between these polymorphisms and the clinical variability.…”
Section: Introductionmentioning
confidence: 99%